Implikasi Teladan Gereja Mula-Mula bagi Kesatuan Jemaat GKE Madara: Refleksi Kisah Para Rasul 2:42-47 - Yola Pradita; Maria Veronica (Integritas: Jurnal Teologi, 2023)
The present day church tends to show a different existence and quality from what was shown by the example of the early church. The feeling of giving and sharing is no longer a priority, unity seems to disappear and ego begins to become a priority. So, the present day church needs to improve itself and have an awareness of the call as followers of Christ to live in unity of faith. Qualitative research based on descriptive analysis methods is carried out in this study. The research area is GKE Madara congregation. This research aims to show an example of early church life based on the reflection of Acts 2:42-47, where this example is applied in the GKE Madara congregation through work programs and daily life. The results of the study show that from an economic, social, human resource and spiritual perspective GKE Madara's unity can be affected by a model of the early church.